Hexacoordinate Ru-based olefin metathesis catalysts with pH-responsive N-heterocyclic carbene (NHC) and N-donor ligands for ROMP reactions in non-aqueous, aqueous and emulsion conditions - Balof, Shawna L.; Nix, K. Owen; Olliff, Matthew S.; Roessler, Sarah E.; Saha, Arpita; Müller, Kevin B.; Behrens, Ulrich; Valente, Edward J.; Schanz, Hans-Jörg (Beilstein Journal of Organic Chemistry, 2015)
Three new ruthenium alkylidene complexes (PCy3)Cl2(H2ITap)Ru=CHSPh (9), (DMAP)2Cl2(H2ITap)Ru=CHPh (11) and (DMAP)2Cl2(H2ITap)Ru=CHSPh (12) have been synthesized bearing the pH-responsive H2ITap ligand (H2ITap = 1,3-bis(2’,6’-dimethyl-4’-dimethylaminophenyl)-4,5-dihydroimidazol-2-ylidene). Catalysts 11 and 12 are additionally ligated by two pH-responsive DMAP ligands. The crystal structure was solved for complex 12 by X-ray diffraction. In organic, neutral solution, the catalysts are capable of performing standard ring-opening metathesis polymerization (ROMP) and ring closing metathesis (RCM) reactions with standard substrates. The ROMP with complex 11 is accelerated in the presence of two equiv of H3PO4, but is reduced as soon as the acid amount increased. The metathesis of phenylthiomethylidene catalysts 9 and 12 is sluggish at room temperature, but their ROMP can be dramatically accelerated at 60 °C. Complexes 11 and 12 are soluble in aqueous acid. They display the ability to perform RCM of diallylmalonic acid (DAMA), however, their conversions are very low amounting only to few turnovers before decomposition. However, both catalysts exhibit outstanding performance in the ROMP of dicyclopentadiene (DCPD) and mixtures of DCPD with cyclooctene (COE) in acidic aqueous microemulsion. With loadings as low as 180 ppm, the catalysts afforded mostly quantitative conversions of these monomers while maintaining the size and shape of the droplets throughout the polymerization process. Furthermore, the coagulate content for all experiments stayed <2%. This represents an unprecedented efficiency in emulsion ROMP based on hydrophilic ruthenium alkylidene complexes.
Keywords: activation; aqueous catalysis; emulsion; olefin metathesis; polymerization; ruthenium

(untitled) - Fogg, D. E.; Conrad, J. C. (Curr. Org. Chem., 2006)

(untitled) - Chatterjee, A. K.; Choi, T.-L.; Sanders, D. P.; Grubbs, R. H. (J. Am. Chem. Soc., 2003)

(untitled) - Wright, D. L. (Curr. Org. Chem., 1999)

Encyclopedia Of Polymer Science and Technology - Nuyken, O.; Schneider, M.; Frenzel, U. (Metathesis Polymerization, 2012)

(untitled) - Leitgelb, A.; Wappel, J.; Slugovc, C. (Polymer, 2010)

(untitled) - Bielawski, C. W.; Grubbs, R. H. (Prog. Polym. Sci., 2007)

(untitled) - Baughman, T. W.; Wagener, K. B. (Adv. Polym. Sci., 2005)

(untitled) - Trimmel, G.; Riegler, S.; Fuchs, G.; Slugovc, C.; Stelzer, F. (Adv. Polym. Sci., 2005)

(untitled) - Gułajski, Ł.; Michrowska, A. M.; Narożnik, J.; Kaczmarska, Z.; Rupnicki, L.; Grela, K. (ChemSusChem, 2008)

(untitled) - Nguyen, S. T.; Johnson, L. K.; Grubbs, R. H.; Ziller, J. W. (J. Am. Chem. Soc., 1992)

(untitled) - Vougiokalakis, G. C.; Grubbs, R. H. (Chem. Rev., 2010)

(untitled) - Anderson, E. B.; Buchmeiser, M. R. (Synlett, 2012)

(untitled) - Tomasek, J.; Schatz, J. (Green Chem., 2013)

(untitled) - Mecking, S.; Held, A.; Bauers, F. M. (Angew. Chem., Int. Ed., 2002)

(untitled) - Fuhrmann, H.; Dwars, T.; Oehme, G. (Chem. Unserer Zeit, 2003)

(untitled) - Pinault, N.; Bruce, D. W. (Coord. Chem. Rev., 2003)

(untitled) - Shaughnessy, K. H. (Chem. Rev., 2009)

(untitled) - Schaper, L.-A.; Hock, S. J.; Herrmann, W. A.; Kühn, F. E. (Angew. Chem., Int. Ed., 2013)

(untitled) - Binder, J. B.; Raines, R. T. (Curr. Opin. Chem. Biol., 2008)

(untitled) - Zaman, S.; Curnow, O. J.; Abell, A. D. (Aust. J. Chem., 2009)

(untitled) - Burtscher, D.; Grela, K. (Angew. Chem., Int. Ed., 2009)

(untitled) - Lynn, D. M.; Mohr, B.; Grubbs, R. H.; Henling, L. M.; Day, M. W. (J. Am. Chem. Soc., 2000)

(untitled) - Lynn, D. M.; Mohr, B.; Grubbs, R. H. (J. Am. Chem. Soc., 1998)

(untitled) - Mohr, B.; Lynn, D. M.; Grubbs, R. H. (Organometallics, 1996)

(untitled) - Saoud, M.; Romerosa, A.; Peruzzini, M. (Organometallics, 2000)

(untitled) - Gallivan, J. P.; Jordan, J. P.; Grubbs, R. H. (Tetrahedron Lett., 2005)

(untitled) - Hong, S. H.; Grubbs, R. H. (J. Am. Chem. Soc., 2006)

(untitled) - Skowerski, K.; Szczepaniak, G.; Wierzbicka, C.; Gułajski, Ł.; Bieniek, M.; Grela, K. (Catal. Sci. Technol., 2012)

(untitled) - Lo, C.; Ringenberg, M. R.; Gnandt, D.; Wilson, Y.; Ward, T. R. (Chem. Commun., 2011)

(untitled) - Samanta, D.; Kratz, K.; Zhang, X.; Emrick, T. (Macromolecules, 2008)

(untitled) - Roberts, A. N.; Cochran, A. C.; Rankin, D. A.; Lowe, A. B.; Schanz, H.-J. (Organometallics, 2007)

(untitled) - Dunbar, M. A.; Balof, S. L.; Roberts, A. N.; Valente, E. J.; Schanz, H.-J. (Organometallics, 2011)

(untitled) - Michrowska, A.; Gułajski, Ł.; Karczmarska, Z.; Mennecke, K.; Kirschning, A.; Grela, K. (Green Chem., 2006)

(untitled) - Binder, J. B.; Guzei, A. I.; Raines, R. T. (Adv. Synth. Catal., 2007)

(untitled) - Rix, D.; Clavier, H.; Coutard, Y.; Gulajski, L.; Grela, K.; Mauduit, M. (J. Organomet. Chem., 2006)

(untitled) - Rix, D.; Caïjo, F.; Laurent, L.; Gulajski, L.; Grela, K.; Mauduit, M. (Chem. Commun., 2007)

(untitled) - Jordan, J. P.; Grubbs, R. H. (Angew. Chem., Int. Ed., 2007)

(untitled) - Leibfarth, F. A.; Mattson, K. M.; Fors, B. P.; Collins, H. A.; Hawker, C. J. (Angew. Chem., Int. Ed., 2013)

(untitled) - Naumann, S.; Buchmeiser, M. R. (Macromol. Rapid Commun., 2014)

(untitled) - Monsaert, S.; Lozano Vila, A.; Drozdzak, R.; Van der Voort, P.; Verpoort, F. (Chem. Soc. Rev., 2009)

(untitled) - Szadkowska, A.; Grela, K. (Curr. Org. Chem., 2008)

(untitled) - Vidavsky, Y.; Anaby, A.; Lemcoff, N. G. (Dalton Trans., 2012)

(untitled) - Schanz, H.-J. (Curr. Org. Chem., 2013)

(untitled) - Wang, D.; Wurst, K.; Knolle, W.; Decker, U.; Prager, L.; Naumov, S.; Buchmeiser, M. R. (Angew. Chem., Int. Ed., 2008)

(untitled) - P’Pool, S. J.; Schanz, H.-J. (J. Am. Chem. Soc., 2007)

(untitled) - Dunbar, M. A.; Balof, S. L.; LaBeaud, L. J.; Yu, B.; Lowe, A. B.; Valente, E. J.; Schanz, H.-J. (Chem. – Eur. J., 2009)

(untitled) - Hahn, F. E.; Paas, M.; Fröhlich, R. (J. Organomet. Chem., 2005)

(untitled) - Samec, J. S. M.; Keitz, B. K.; Grubbs, R. H. (J. Organomet. Chem., 2010)

(untitled) - Bienik, M.; Bujok, R.; Cabaj, M.; Lugan, N.; Lavigne, G.; Arlt, D.; Grela, K. (J. Am. Chem. Soc., 2006)

(untitled) - Gawin, R.; Makal, A.; Woźniak, K.; Mauduit, M.; Grela, K. (Angew. Chem., Int. Ed., 2007)

(untitled) - Pietraszuk, C.; Rogalski, S.; Powała, B.; Miętkiewski, M.; Kubicki, M.; Spólnik, G.; Danikiewicz, W.; Woźniak, K.; Pazio, A.; Szadkowska, A.; Kozłowska, A.; Grela, K. (Chem. – Eur. J., 2012)

(untitled) - Monsaert, S.; Ledoux, N.; Drozdzak, R.; Verpoort, F. (J. Polym. Sci., Part A: Polym. Chem., 2010)

(untitled) - Rouen, M.; Queval, P.; Falivene, L.; Allard, J.; Toupet, L.; Crévisy, C.; Caijo, F.; Baslé, O.; Cavallo, L.; Mauduit, M. (Chem. – Eur. J., 2014)

(untitled) - Claverie, J. P.; Viala, S.; Maurel, V.; Novat, C. (Macromolecules, 2001)

(untitled) - Quémener, D.; Héroguez, V.; Gnanou, Y. (Macromolecules, 2005)

(untitled) - Öztürk, B. Ö.; Şehitoğlu, S. K.; Meier, M. A. R. (Eur. Polym. J., 2015)

(untitled) - Sanford, M. S.; Love, J. L.; Grubbs, R. H. (J. Am. Chem. Soc., 2001)

(untitled) - Kovačič, S.; Krajnc, P.; Slugovc, C. (Chem. Commun., 2010)

(untitled) - Quémener, D.; Héroguez, V.; Gnanou, Y. (J. Polym. Sci., Part A: Polym. Chem., 2006)

(untitled) - Quémener, D.; Chemtob, A.; Héroguez, V.; Gnanou, Y. (Polymer, 2005)

(untitled) - Balof, S. L.; P’Pool, S. J.; Berger, N. J.; Valente, E. J.; Schiller, A. M.; Schanz, H.-J. (Dalton Trans., 2008)

(untitled) - Balof, S. L.; Yu, B.; Lowe, A. B.; Ling, Y.; Zhang, Y.; Schanz, H.-J. (Eur. J. Inorg. Chem., 2009)

(untitled) - Leuthäußer, S.; Schmidts, V.; Thiele, C. M.; Plenio, H. (Chem. – Eur. J., 2008)

(untitled) - Trnka, T. M.; Morgan, J. P.; Sanford, M. S.; Wilhelm, T. E.; Scholl, M.; Choi, T.-L.; Ding, S.; Day, M. W.; Grubbs, R. H. (J. Am. Chem. Soc., 2003)

(untitled) - van der Schaaf, P. A.; Kolly, R.; Kirner, H.-J.; Rime, F.; Mühlebach, A.; Hafner, A. (J. Organomet. Chem., 2000)

(untitled) - Wallace, D. J. (Adv. Synth. Catal., 2009)

(untitled) - Dias, E. L.; Nguyen, S. T.; Grubbs, R. H. (J. Am. Chem. Soc., 1997)

(untitled) - Peeck, L. H.; Leuthäusser, S.; Plenio, H. (Organometallics, 2010)

(untitled) - Ritter, T.; Hejl, A.; Wenzel, A. G.; Funk, T. W.; Grubbs, R. H. (Organometallics, 2006)

(untitled) - Davidson, T. A.; Wagener, K. B.; Priddy, D. B. (Macromolecules, 1996)

(untitled) - Van Ornum, S. G.; Cook, J. M. (Tetrahedron Lett., 1996)

(untitled) - Hudson, D. M.; Valente, E. J.; Schachner, J.; Limbach, M.; Müller, K.; Schanz, H.-J. (ChemCatChem, 2011)